Gen Z Tax Compliance: The Role of Digital Literacy and Coretax - Nurimansyah Mapparenta, Muwaffiq; Riski Ananda, Sukma; Arham, Arham (Amsir Management Journal, 2026)
This study examines the effect of digital literacy and Coretax understanding on tax compliance among Generation Z students at the Faculty of Economics and Business, Universitas Muslim Indonesia. A quantitative explanatory research design was employed, involving 90 respondents selected through purposive sampling. Data analysis was conducted using SMART PLS. The results reveal that digital literacy has a positive and significant effect on tax compliance, indicating that students’ ability to use digital technologies contributes to improved compliance behavior. Conversely, Coretax understanding shows a positive but insignificant effect on tax compliance, suggesting that technical familiarity with the Coretax system has not yet directly influenced the compliance behavior of Generation Z. The study concludes that digital literacy plays a crucial role in supporting digital transformation in taxation, whereas the implementation of Coretax still requires stronger educational support and greater user readiness, particularly among younger taxpayers.